Individual and mixture effect of selected high-hazard pharmaceuticals on aquatic primary producers - Montiel Mora, José Rolando (2025)
The extensive use of pharmaceuticals has led to their occurrence in surface waters due to insufficient treatment processes for their removal. Their environmental impact remains largely unexplored for certain trophic levels, particularly plants and algae. Pharmaceuticals often occur in mixtures with other pollutants, highlighting the need for comprehensive toxicological ssessments that evaluate their combined interactions. This study evaluated the acute toxicity of four high-hazard pharmaceuticals —diphenhydramine, fluoxetine, ketoprofen, and trimethoprim— and their binary mixtures, on the green microalgae Raphidocelis subcapitata and the aquatic macrophyte Lemna gibba. For individual compounds, R. subcapitata growth rate was inhibited in all cases, with fluoxetine, ketoprofen and diphenhydramine exhibiting moderate toxicity (EC 50 = 0.34, 0.14, and 4.88 mg/L, respectively), while trimethoprim showed low toxicity (EC 50 = 332.35 mg/L). Similar trends were observed in L. gibba, except for diphenhydramine, which also showed low toxicity (EC 50 = 26.57 mg/L). Binary mixtures demonstrated a synergistic interaction towards the microalgae in the presence of ketoprofen, except ketoprofen-trimethoprim combination (antagonism, p < 0.0001). In contrast, most interactions in L. gibba exhibited antagonism, except ketoprofen-fluoxetine (synergism, p = 0.0042). Differences were observed between the two model organisms for individual compounds and mixtures. No correlation was found between L. gibba experimental data and QSAR predictions derived from R. subcapitata. Our results highlight the need for: i. further studies including mixtures of relevant pharmaceuticals; ii. caution in the use of predictive models or extrapolation between taxa; and iii. the inclusion of fluoxetine and ketoprofen as priority compounds in future risk assessments.